2020
DOI: 10.1007/s11273-020-09719-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of airborne hyperspectral data for mapping of invasive alien Spiraea tomentosa L.: a serious threat to peat bog plant communities

Abstract: Remote sensing is increasingly widely used in nature conservation management. The research focuses on developing an optimal set of airborne raster data for the identification of the invasive alien species Spiraea tomentosa L. The plant species selected for the purposes of this study poses a serious threat to peat bog plant communities, moist coniferous forests, and meadows in Central Europe. The impact of the data acquisition time on the accuracy of classification and the percentage cover limit required for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
3
10
0
Order By: Relevance
“…In the case of the SVM classifier, MNF-based results were the worst (HySpex: 78.5%; and 69.7% for MNF). Similar observations were made by Kopeć et al [85], who used HySpex images as well. In this case, the MNF-based classifications identified invasive and expansive species.…”
Section: Discussionsupporting
confidence: 85%
“…In the case of the SVM classifier, MNF-based results were the worst (HySpex: 78.5%; and 69.7% for MNF). Similar observations were made by Kopeć et al [85], who used HySpex images as well. In this case, the MNF-based classifications identified invasive and expansive species.…”
Section: Discussionsupporting
confidence: 85%
“…Lower accuracies might be caused by using referenced data that included reference polygons with relatively low density of Calamagrostis epigejos (40%). In frame of the same project Kopeć et al [20] has shown that minimum density of abovementioned plant species should be no less than 70% in order to be properly identified. Moreover, past research of Sabat-Tomala et al [32] has also shown that SVM classifier is more suited for identification of Calamagrostis epigejos than random forest (SVM F1-score-0.91 and RF F1-score-0.83).…”
Section: Discussionmentioning
confidence: 99%
“…For example, The SVM algorithm and the recursive feature elimination (SVM-RFE) approach were used to map the species Solanum mauritianum in KwaZulu Natal (eastern parts of South Africa) with an overall accuracy (OA) of 93% on selected 17 hyperspectral bands of the AISA Eagle image [19]. The random forest algorithm and 25 MNF bands of HySpex images for mapping the species Spiraea tomentosa in the Lower Silesian forests in Poland was used to obtain an F1-score accuracy for the species of 83% (OA-99%) for September's images and an F1-score of 77% (OA-99%) for August's [20]. Most studies indicate the need for methods that reduce the spectral space of hyperspectral imaging, e.g., principal component analysis (PCA) and minimum noise fraction (MNF), in order to reduce the data volume and shorten the data processing time [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…RS has become a widely applied tool in plant studies (e.g. Asner, Hughes, et al., 2008; Asner et al., 2008; Kopeć et al., 2020; Wan et al., 2020) with the increasing availability of RS products that capture a wide variety of environmental features (Corbane et al., 2015; Kerr & Ostrovsky, 2003; Turner et al., 2003). Studies using RS to focus specifically on rare plants remain uncommon, although their number has been growing in recent years (e.g.…”
Section: Introductionmentioning
confidence: 99%